Optimising Vine Growth, Marketable Tuber Yield, and Biomass Production of Orange-Fleshed Sweet Potato Through Tillage and Fertilizer Management in FCT-Abuja, Nigeria - Ilozobhie, Nicholas Eronmonsele; Aihebhoria, Daniel Osabhie; Awojemila, Franklin Adekunle; Baba-Nitsa, Mohammed; Usman, Bilqis Ejura; Akpan, Glory Ephraim; Azzuwut, Promise Andrew; Okoro, Cynthia Oluchi (FUDMA Journal of Sciences, 2026)
Orange-fleshed sweet potatoes (OFSP) are widely promoted in sub-Saharan Africa to improve vitamin A intake. However, production is constrained by poor soil fertility and tillage practices in Nigeria’s Federal Capital Territory (FCT). This research determined the combined effects of three tillage practices (mound, ridge and flat-bed) and four fertilizer treatments (NPK 20: 10:10 at 200 kg/ ha; poultry manure at 5 t/ha, urea at 200 kg/ha and unfertilized control) on growth, yield and pest incidence of OFSP cultivar Mother’s Delight during the 2024 and 2025 cropping seasons at University of Abuja Teaching and Research Farm on factorial combination of 3 x 4 in randomized complete block design with three replicates. Tillage combined with NPK fertiliser application increased vine length (233.7 cm), leaf number (174.1), and fresh biomass yield (9.4 kg/plot) by 76%, 86%, and 62%, respectively, over the control. Root yield was highest in mound tillage (29.4 t/ha), while the maximum storage root yield of 38.5 t/ha was obtained from the mound–NPK interaction, representing a 92% improvement over the flat-bed control treatment. Application of poultry manure shifted soil pH (4.6–6.7) and increased cation exchange capacity (CEC) to 3.78 cmol/kg, indicating improved soil fertility. However, the incidence of Cylas weevil infection was increased by 84% with the use of NPK fertilizer. Fresh biomass had a positive correlation with marketable roots (r = 0.971, r = 0.900, respectively). Mound tillage coupled with the application of NPK fertilizer would increase OFSP yield significantly.